Paclobutrazol mitigates salt stress in indica rice seedlings by enhancing glutathione metabolism and glyoxalase system - Bundit Khunpon (2018)
© 2018, Institute of Molecular Biology, Slovak Academy of Sciences. Stress-induced methylglyoxal (MG) functions as a toxic molecule, inhibiting plant physiological processes such as photosynthesis and antioxidant defense systems. In the present study, an attempt was made to investigate the MG detoxification through glutathione metabolism in indica rice [Oryza sativa L. ssp. indica cv. Pathumthani 1] under salt stress by exogenous foliar application of paclobutrazol (PBZ). Fourteen-day-old rice seedlings were pretreated with 15 mg L−1 PBZ foliar spray. After 7 days, rice seedlings were subsequently exposed to 0 (control) or 150 mM NaCl (salt stress) for 12 days. Prolonged salt stress enhanced the production of MG molecules and the oxidation of proteins, leading to decreased activity of glyoxalase enzymes, glyoxalase I (Gly I) and glyoxalase II (Gly II). Consequently, the decreased glyoxalase activities were also associated with a decline in reduced glutathione (GSH) content and glutathione reductase (GR) activity. PBZ pretreatment of rice seedlings under salt stress significantly lowered MG production and protein oxidation, and increased the activities of both Gly I and Gly II. PBZ also increased GSH content and GR activity along with the up-regulation of glyoxalase enzymes, under salt stress. In summary, salinity induced a high level of MG and the associated oxidative damage, while PBZ application reduced the MG toxicity by up-regulating glyoxalase and glutathione defense system in rice seedlings.